Provisional Agenda for the Thirty-Second Meeting of the International Monetary and Financial Committee. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
The following is the provisional agenda for the Thirty-Second Meeting of the International Monetary and Financial Committee, which is to be convened in Lima, Peru, October 9-10, 2015.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet